Optimization and Comparison of Drying Methods of Ultrafiltered Soy Protein Solution Using Response Surface Methodology - John, Hima; Sain, Mukul; Mansuri, Shekh Mukhtar; Ray, Arijit; N, Banasree; Sinha, L. K. (Annals of Arid Zone, 2024)
The escalating significance of plant-based protein sources, particularly soy proteins, mirrors the evolving health perspectives of individuals. As protein powders continue to be embraced for direct consumption or incorporation into diverse food matrices, the present study addresses the pivotal process of drying soy protein solutions. Employing the ultrafiltration membrane technique, we explored the efficacy of both spray drying and oven drying methods, meticulously optimizing the drying parameters. In our investigation, we sought to gauge the overall protein yield, benchmarking against the protein content of the raw material, defatted soy flour (DSF). The comparative analysis with the freeze-dried counterpart revealed distinctive outcomes. The freeze dryer exhibited an overall protein yield of 54%, surpassing its counterparts. The oven dryer yielded a respectable 48%, while the spray dryer, though yielding 33%, presented an alternative perspective. These findings underscore the meticulous considerations in selecting drying methods for soy protein solutions, acknowledging the trade-off between different techniques.